REPRESENTATIVENESS BIAS IN SYLVIA TOWNSEND WARNER’S THE PHOENIX - Pasopati, Rommel Utungga; Aulia, Annisa Deby; Kartiningsih, Rindrah; Andharu, Devito; Fadillah, Muhammad Reza Ishadi (LPPM Universitas PGRI Jombang, 2025)
Representativeness bias occurs when possible similarity of an object shadows the real condition. This mental shortcut, as accentuated by Amos Tversky and Daniel Kahneman, is affiliated with Gambler’s Fallacy. The Phoenix is Sylvia Townsend Warner’s short story released in 1940. This story tells about a phoenix set on a display to the audience. The owner wanted to kill it since its death would show amusement of fire. The phoenix died as the fire came out and burned the place including the owner and the spectators. Then, how is representative bias illustrated on Sylvia Townsend Warner’s The Phoenix? Through qualitative methods on psychological and literary studies, this article asserts the owner’s misconception of the phoenix. The bird’s specialty was its rare exoticness and myth about being immortal. The owner was shadowed with greed by opposing the true state of nature. He then had to accept the bitter truth of death as the pyre burned all out including himself and other persons. In conclusion, the story shows how representative bias accompanied with greedy thought may ignore otherness by accentuating mere profit.